Intelligence of visually impaired children: Assessment considerations - Gabrialavičiūtė, Ingrida (Psichologija, 2007)
Problems and possibilities assessing intellectual abilities of visually impaired children are addressed in the article. In other countries, usually, there are few or no nationally standardized tests available for use with this population. Therefore parts of available instruments designed for normally sighted children are used. Sometimes test procedures or stimuli are modified what affects the validity of the results and they need to be interpreted with caution. Intellectual abilities of Lithuanian visually impaired children are currently assessed using WISC-III Verbal scale. We discuss the possibility to use ITVIC (Intelligence test for visually impaired children) test for the assessment of intellectual abilities of Lithuanian children. ITVIC was designed in The Netherlands for an assessment of intellectual abilities of Braille educated visually impaired children aged 6–15 years. The authors used Thurstone Primary factor theory as a theoretical starting point. ITVIC has both, verbal and haptic subtests and two types of norms: age norms for all Braille educated children and age norms for two vision groups within the population of Braille educated children separately. ITVIC Manual is translated to English which made it accessible for use in Lithuania. After we received the permission from publishers and test author, translation of ITVIC manual was made. Based on results from 41 Lithuanian Braille educated children aged 7–16 years, evaluation of ITVIC reliability and validity was made. Data analysis based on the method of internal consistency and Split half reliability analysis confirmed good reliability of all ITVIC subtests except House plan questions. This subtest also has low content validity. Correlations between ITVIC subtests and school achievement results show adequate criterion validity of the test. The means of subtest scores in Lithuanian and Dutch population were compared for the group of children without usable vision aged >13,5 years. The scores of two WISC-III subtests as part of ITVIC test were compared to Lithuanian WISC-III norms. The results show that the results of 7 ITVIC subtests can be interpreted using Duch norm tables and Lithuanian WISC-III Vocabulary norms for this age group.